1990
DOI: 10.1007/bf01344310
|View full text |Cite
|
Sign up to set email alerts
|

Activities of metabolic enzymes in the deep-water crabsChaceon fenneri andC. quinquedens and the shallow-water crabCallinectes sapidus

Abstract: Abstract. The activities of 18 enzymes were measured in gill, hepatopancreas and muscle tissue of the deep-water crabs Chaceon fenneri and C. quinquedens and the shallow-water crab Callinectes sapidus collected from the Gulf of Mexico in January 1989. The activities of catabolic enzymes were correlated in general with the known metabolic rates of the three species. Activities were much higher in C. sapidus than in Chaceon fenneri and C. quinquedens. In some cases, C. quinquedens had higher activities than C. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…3 & 4). Our results indirectly support the hypothesis of Seibel & Walsh (2001) that deep-sea animals exchange ions at the gills more slowly than their shallow-living counterparts, and are consistent with a general pattern of reduced rates of key metabolic and enzymatic processes in deep-sea decapod crabs, compared to shallow-living species , Walsh & Henry 1990. Bicarbonate acquisition, the primary means of pH compensation in aquatic animals, was not observed in Tanner crabs acclimated to low oxygen, suggesting a marked reduction (or delay) in ion exchange.…”
Section: Discussionsupporting
confidence: 87%
“…3 & 4). Our results indirectly support the hypothesis of Seibel & Walsh (2001) that deep-sea animals exchange ions at the gills more slowly than their shallow-living counterparts, and are consistent with a general pattern of reduced rates of key metabolic and enzymatic processes in deep-sea decapod crabs, compared to shallow-living species , Walsh & Henry 1990. Bicarbonate acquisition, the primary means of pH compensation in aquatic animals, was not observed in Tanner crabs acclimated to low oxygen, suggesting a marked reduction (or delay) in ion exchange.…”
Section: Discussionsupporting
confidence: 87%
“…1 & 5). A similar scope of 1.5-to 20-fold lower activity was found in an assortment of metabolic enzymes from the deep-sea crabs Chaceon fenneri and Chaceon quinquedens, when compared to the sublittoral Callinectes sapidus (Walsh & Henry 1990).…”
Section: Discussionsupporting
confidence: 66%
“…A previous report comparing 2 species of deep-sea crabs of the genus Chaceon with the sublittoral Callinectes sapidus concluded that activities of specific metabolic enzymes were generally much lower in the deep-sea decapod species (Walsh & Henry 1990).…”
Section: Introductionmentioning
confidence: 92%
“…Benthic species are better represented by measurements of metabolic enzyme activities that serve as proxies for metabolic capacity. The majority of oxygen consumption and aerobic metabolic enzyme measurements in deep-sea benthic species, including echinoderms (Smith 1983), meiobenthic animals (Shirayama 1992), crabs and shrimp (Childress & Mickel 1985;Henry et al 1990;Walsh & Henry 1990;Childress et al 1990a;Bailey et al 2005), amphipods (Smith & Baldwin 1982;Treude et al 2002), sponges (Witte & Graff 1996) and octopods were at most oneto fivefold lower than shallow-living species after temperature correction and many of these groups show no decline at all (e.g. figures 1c, 2, 3c and 4).…”
Section: Rates Of Metabolism In Relation To Environmental Variablesmentioning
confidence: 99%